Penambahan Media Kapas Dan Kerikil Pada Multi Tray Aerator Untuk Pengolahan Air Daerah Rususnawa Untan Dalam Mengurangi Kandungan Logam Sebagai Pre-treatment Pada Sistem Membran RO - Apriyantine, Apriyantine; Danial, M Meddy; Purnaini, Rizki (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
Rivers are surface water used for public purposes. Rivers are used for water storage, transportation, irrigation, livestock, industry, housing, water availability, fish rearing and recreation. Various activities carried out in the river cause pollution and have an impact on the decline in water quality, such as in Sepakat 2 river water which is used by the surrounding community for daily needs. The purpose of this study was to determine the Fe contained in Sepakat 2 river water and the effectiveness of using multi tray aerators with the addition of cotton and gravel media in reducing iron levels. Processing of Sepakat 2 river water through a pretreatment process using a 5-level multi tray aerator method and 6 perforated trays to drop water to the bottom of the container, then the water that has been aerated is collected in a box and deposited for 1 and 2 hours after which the water is taken and stored using a bottle container to be analyzed by the Pontianak Industrial Standardization and Services Center Laboratory. The results of this study are the quality of river water Sepakat 2 iron levels 6.37 mg / L before processing, after aeration 4.99 mg / L, after settling 1 and 2 hours with the same value of 5.09 mg / L. The efficiency of the multi tray aerator tool to reduce iron parameters from iron by 20.09%, TDS 52.1%, mercury (Hg) 43.08% and salinity is 63.3%.